The need for speed: observational study of physician driving behaviors. (18th December 2019) - Zimerman, André; Worsham, Christopher; Woo, Jaemin; Jena, Anupam B
Abstract: Objective: To determine whether fast driving, luxury car ownership, and leniency by police officers differ across medical specialties. Design: Observational study. Setting: Florida, USA. Participants: 5372 physicians and a sample of 19 639 non-physicians issued a ticket for speeding during 2004-17. Main outcome measures: Observed rates of extreme speeding (defined as driving >20 mph above the speed limit), luxury car ownership, and leniency of the speeding ticket by police officers, by physician specialty, after adjustment for age and sex. Results: The sample included 5372 physicians who received 14 560 speeding tickets. The proportion of drivers who were reported driving at speeds greater than 20 mph was similar between physicians and a sample of 19 639 non-physicians who received a ticket for speeding (26.4% v 26.8% of tickets, respectively). Among physicians who received a ticket, psychiatrists were most likely to be fined for extreme speeding (adjusted odds ratio of psychiatry compared with baseline specialty of anesthesia 1.51, 95% confidence interval 1.07 to 2.14). Among drivers who received a ticket, luxury car ownership was most common among cardiologists (adjusted proportion of ticketed cardiologists who owned a luxury car 40.9%, 95% confidence interval 35.9% to 45.9%) and least common among physicians in emergency medicine, family practice, pediatrics, general surgery, and psychiatry (eg, adjusted proportion of luxury car ownership among family practice physicians 20.6%, 95% confidence interval 18.2% to 23.0%). Speed discounting, a marker of leniency by police officers in which ticketed speed is recorded at just below the threshold at which a larger fine would otherwise be imposed, was common, but rates did not differ by specialty and did not differ between physicians and a sample of non-physicians. Conclusions: Rates of extreme speeding were highest among psychiatrists who received a ticket, whereas cardiologists were the most likely to be driving a luxury car when ticketed. Leniency by police officers was similar across specialties and between physicians and non-physicians.